2000
DOI: 10.1614/0043-1745(2000)048[0680:aatote]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Absorption and translocation of triclopyr ester inPopulus tremuloides

Abstract: The effect of three spray variables (droplet number, active ingredient concentration, and droplet size) on uptake and translocation of formulated 14C-triclopyr ester was studied in greenhouse-grown Populus tremuloides seedlings. The dose per plant in all treatments was held constant. In all experiments, absorption (as a percentage of dose applied) was much greater than translocation (as percentage of dose absorbed). Absorption and translocation decreased as concentration (ai) was increased and droplet number d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 11 publications
(15 reference statements)
0
4
0
Order By: Relevance
“…(Aliverdi and Karami 2020). This is also true for other groups (mode of actions) of herbicides against easy-to-wet species (Knoche 1994;Huang et al 2000;Shaw et al 2000;Sasaki et al 2013;Creech et al 2015;Meyer et al 2016). Due to a low level of energy existing in smaller spray droplets, they can easily be deposited on the leaf surface, leading to greater efficacy of the herbicide (Penner 2000).…”
Section: Resultsmentioning
confidence: 97%
“…(Aliverdi and Karami 2020). This is also true for other groups (mode of actions) of herbicides against easy-to-wet species (Knoche 1994;Huang et al 2000;Shaw et al 2000;Sasaki et al 2013;Creech et al 2015;Meyer et al 2016). Due to a low level of energy existing in smaller spray droplets, they can easily be deposited on the leaf surface, leading to greater efficacy of the herbicide (Penner 2000).…”
Section: Resultsmentioning
confidence: 97%
“…While concentration is expected to have an important influence on foliar uptake, its effect on uptake of many agrochemicals is largely unknown (Wang & Liu, 2007 ). Furthermore, its effect on uptake can be dependent on droplet size and number (Huang, Campbell, Studens, & Fleming, 2000 ), an aspect which was not examined in this study. This study indicated that for triclopyr applied as an ester to P. contorta needles, uptake generally decreased with increasing concentration, particularly above 3%.…”
Section: Discussionmentioning
confidence: 98%
“…In a study that examined absorption and translocation of triclopyr ester in Populus tremuloides , Huang et al. ( 2000 ) found that absorption and translocation of triclopyr decreased as concentration increased and droplet size decreased. Absorption and translocation also decreased as droplet number decreased and droplet size increased (while concentration was held constant).…”
Section: Discussionmentioning
confidence: 99%
“…Triclopyr work through selectivity of woody and herbaceous broadleaf plants, systemic movement and Auxin mimicking [ 53 , 65 ]. High accumulation and activity of Auxin (IAA) during the tender growth stage influences the potential efficacy of triclopyr through mimicking auxin hormone [ 63 , 66 , 67 ]. Nevertheless, less accumulation and activity of IAA during mature and blooming stages, reduces efficient performance of triclopyr [ 47 , 68 ].…”
Section: Discussionmentioning
confidence: 99%